MULTICULTURAL ISLAMIC EDUCATIONS’ VALUES AND CHARACTER OF HUBBUL WATHON BASED OF MADRASAH’S LOCAL WISDOM - Afandi Afandi (Universitas Islam Malang, 2021)
Madrasah is a national education unit that has an important role in the character education of Hubbul Wathon. Madrasah based Pesantren is a unique model for the archipelago. The integration model of educational institutions provides educational comprehensiveness, especially in the praxis of Multicultural Islamic Education is maintained by madrasas. The purpose of this research is to find out about; the values of Multicultural Islamic education developed in Madrasah Aliyah Nurulhuda Pakandangan Sumenep and Madrasah Aliyah Mambaul Ulum Bata-Bata Pamekasan; the integration of the values of Multicultural Islamic Education based of Madrasah’s local wisdom. The research method used is qualitative with a phenomenological approach. Determination of informants was carried out by using a full purpose sample strategy and snow ball sampling. The data network was carried out by observation, in-depth interviews, FGD and documentation. Data analysis used Miles and Hubarman’s analysis, reduction, display and verification. The results of the study show that the values of the Multicultural Islamic Religious Education done by Madrasah are religiosity (al-Rabbaniyah), humanity (al-Insaniyah), social discipline and solidarity, justice. and equality, Tolerance and harmony, Social Care (mutual cooperation), Service, Comprehension (al-Symuliyah), and State Defense, Keywords: Multicultural Islamic Education, Character, Hubbul Wathon, Local Wisdom, Madrasah